Determination of Ethambutol in Aqueous Medium Using an Inexpensive Gold Microelectrode Array as Amperometric Sensor - Lima, A. E. B.; Luz, G. E.; Batista, N. C.; Longo, E. [UNESP]; Cavalcante, L. S.; Santos, R. S. (Wiley-Blackwell, 2016)
In this paper, gold microelectrode array (Au-MEA) were employed to determination of ethambutol in aqueous medium. Au-MEA was constructed with an electronic microchip integrated circuit. The standard curve (analytical curve) was constructed for a single microelectrode (ME) in a concentration range of 5.0 x 10(-5) to 2.0 x 10(-3) molL(-1), allowing estimation of both the limit of detection (LOD) (4.73 x 10(-5) molL(-1)) and the limit of quantification (LOQ) (1.57 x 10(-4) molL(-1)) for ethambutol. When the MEA was utilized, the LOD and LOQ were 1.55 x 10(-7) and 5.18 x 10(-7) molL(-1), respectively. Our results indicated that Au-MEA can be utilized as amperometric sensors for ethambutol determination in aqueous
Keywords: Amperometric Sensor; Gold microelectrode array; Ethambutol